Union of the Comoros : 2004 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that economic developments in the Union of the Comoros during 2003 were adversely affected by the difficult relationship between the Union and island governments. The related disputes regarding competencies and resources prevented the design and implementation of coherent economic policies, brought to a virtual standstill structural reforms, and undermined confidence at home and abroad, with adverse consequences for private investment and foreign aid. As a result, the Comoros real per capita income declined for the sixth year in a row.